A survey of the participation in competitive sports despite musculoskeletal complaints. Issue 4 (27th March 2011) - Lopes, A D; Barreto, H J; Neto, J O; Neto, JG
Abstract : Background: It is not unusual for athletes to decide to participate in important competitions, despite an ongoing disability or injury. Objective: Evaluate the degree of confidence exhibited by injured athletes with regards to their participation in a major competition, and to profile the musculoskeletal injuries. Design: A cross-sectional survey was conducted with the athletes of the Brazilian delegation participating in the IX South American Games, and 2nd Lusophony Games who sought care from the Brazilian team's medical department with various musculoskeletal complaints. Setting: A group of elite athletes prior to the start of an official competition. Participants: Of the 697 participants in the Brazilian delegation to the IX South American Games (Medellin, 2010) and 2nd Lusophony Games (Lisbon, 2009), 98 athletes (14.6%) sought care from the Brazilian team's medical department with various musculoskeletal complaints, even before commencing participation in the competition. Main outcome measurements: Degree of confidence exhibited by injured athletes and the profile of the musculoskeletal injuries. Results: Regarding the onset of injury, the 98 (14.6% of the 697 total participants) injured athletes who sought care from the medical staff, 57.1% of the athletes had been injured for longer than two months (n=56). Approximately half (n=44, 44.9%) reported that the injury was recurrent. The most frequently occurring injury was tendinopathy (n=33, 27.5%), and the most frequent location of injury was the knee (n=20, 18%). Conclusions: We could observe that many athletes participating in a major competition even with existing musculoskeletal complaints were worried about their injuries affecting their well-being and performance. The majority of these athletes had been injured for longer than two months. Approximately half of them reported that the injury was recurrent. The most frequently occurring lesion was tendinopathy, and the most frequent location of injury was the knee.